2021
DOI: 10.17533/udea.rfnsp.e346540
|View full text |Cite
|
Sign up to set email alerts
|

Barreras para la atención de las conductas suicidas en Ciudad de México: experiencias del personal de salud en el primer nivel de atención

Abstract: Objetivo: Identificar las barreras que existen para la atención de las conductas suicidas, desde la perspectiva de las/los profesionales de la salud mental del primer nivel de atención de la Ciudad de México. Metodología: Estudio cualitativo exploratorio, basado en 35 entrevistas semiestructuradas, dirigidas a personal de salud de dos unidades de salud mental de referencia nacional. El análisis de la información se hizo mediante el Framework Analysis. Resultados: Las/los participantes consideraron que las cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Some authors (Chu et al, 2017) have pointed out that smaller effect sizes are usually found when suicide research is not based solely on the web, so it could be deduced that the privacy and anonymity of social networks could be providing more reliable information, less susceptible to effects of social desirability, in such a way those information gathering strategies could be maintained in a virtual format even without the impediment to carrying out face-to-face evaluations; In addition to the fact that some preventive strategies have already been developed within virtuality, an example of this has been focusing on social connectivity as a protection factor, through the creation of safe environments in spaces such as Reddit (McAuliffe et al, 2022). Suicide is complex and multifactorial, so it requires an approach that is not limited only to psychopathology, it is necessary that prevention considers the socioeconomic and cultural context (Gómez-García et al, 2022;Navarrete et al, 2019 ), in this sense, it is essential to prevent suicide to move towards multidisciplinary approaches that are not only the responsibility of public health instances, it is necessary to promote laws and a legal framework that allows establishing solid strategies against suicide in favor of mental health (Valdéz-Santiago et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (Chu et al, 2017) have pointed out that smaller effect sizes are usually found when suicide research is not based solely on the web, so it could be deduced that the privacy and anonymity of social networks could be providing more reliable information, less susceptible to effects of social desirability, in such a way those information gathering strategies could be maintained in a virtual format even without the impediment to carrying out face-to-face evaluations; In addition to the fact that some preventive strategies have already been developed within virtuality, an example of this has been focusing on social connectivity as a protection factor, through the creation of safe environments in spaces such as Reddit (McAuliffe et al, 2022). Suicide is complex and multifactorial, so it requires an approach that is not limited only to psychopathology, it is necessary that prevention considers the socioeconomic and cultural context (Gómez-García et al, 2022;Navarrete et al, 2019 ), in this sense, it is essential to prevent suicide to move towards multidisciplinary approaches that are not only the responsibility of public health instances, it is necessary to promote laws and a legal framework that allows establishing solid strategies against suicide in favor of mental health (Valdéz-Santiago et al, 2021).…”
Section: Discussionmentioning
confidence: 99%